Data intensive computing applications for big data - Mittal, Mamta (IOS Press, 2018)
The book 'Data Intensive Computing Applications for Big Data' discusses the technical concepts of big data, data intensive computing through machine learning, soft computing and parallel computing paradigms.It brings together researchers to report their latest results or progress in the development of the above mentioned areas.